RANCANGAN ALAT SIKLIK VOLTAMMOGRAM UNTUK APLIKASI PADA PENGUKURAN SEL SUPERKAPASITOR - A. A. Yani; E. Taer; R. N. Saputra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
An instrument has been made to measure the voltage and current of supercapacitor cellusing a cyclic voltammetry technique. This instrument consists of a potentiostat and asignal conditioner. Data processing and analyzing were performed using data acquisitionsystem of a 12-bit serial ADC type ADS 7476. The ADC circuit a does not have a registerthat why it is controlled directly by a microcontroller ATmega8. This circuit was used asanalog data converter of supercapacitor cells into digital data. The output voltage of theamplifier of supercapacitor cell was acquired by the ADC before it was interfaced tomicrocontroller. Data obtained from the ADC was sent by the microcontroller to acomputer with an RS232 serial cable and read using Visual Studio C++. The programsoftware Visual Studio C++ controled the retrieval of data by selecting a microcontrollerand gain amplifier programmable which was appropriate that the received signal dataacquisition system becomes more optimal. The read data was stored in the database andthen visualized in the form of graphs and tables of voltammogram measurement data. Thetests conducted in this study was a testing of microcontroller, a signal conditioning andinstrumentation overall. Prototypes of this instrument were tested on a modified carbonelectrode with a mixture substance of CNTs10%, PANI 15%, PVDF 5%, and 70% ofactivated carbon from cassava. The supercapacitor cell was assembled in the form of coins,which comminuted of ribbon Stailess steel (316L) as a current collector, a 1M H 2 SO 4electrolyte and a carbon composite as a working electrode. The measurement of currentobtained a current in the range of -1mA to 0.993 mA at a voltage between 0 Volt to 0.5Volt from a voltammogram curve. The result obtained was then composed with theinstrument tool of the commercial potentiostat. Error percentage of all measurements was ±6.05%.